Analysis of the implementation of drug inventory control using the ABC-EOQ-ROP method at Sundari Hospital Medan - Kaban, Lyta Imanti; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Science Midwifery, 2025)
Pharmaceutical supplies are one of the resource elements that must be controlled in the operational management of a hospital to support hospital services in order to provide maximum health services. The study aims to analyze the Implementation of Drug Inventory Control with the ABC-EOQ-ROP method at Sundari Hospital, Medan. The research method used was descriptive qualitative which was carried out at Sundari Hospital, Medan in October-November 2024. Informants were the head of the pharmacy installation, pharmacy staff, and head of the room. Data were analyzed using interactive analysis. The results of the study showed that the availability of drugs before the implementation of the EOQ and ROP methods based on the type and quantity of drugs was not sufficient to meet the needs where there were still some drugs that could not be met in a timely manner. The availability of drugs after the implementation of the EOQ and ROP methods in the pharmacy warehouse when viewed based on the type and quantity of drugs was sufficient to meet the needs of the pharmacy installation in a timely manner. It is recommended that drug inventory control in this study only emphasizes the calculation of drug inventory control that requires greater management (category I) quantitatively.